Periodicity and abundance of plankton in a peninsular river of India - Singh, D N; Das, A K (Indian Journal of Fisheries, 2011)
Study on periodicity and abundance of plankton in Cauvery River revealed phytoplankton dominance (88.19% to 96.03%) during pre-monsoon, monsoon and post-monsoon periods. Plankton population was rich during monsoon followed by pre-monsoon and post-monsoon. Among phytoplankton, bacillariophyceae dominated during pre-monsoon (69.12%) and post-monsoon (59.87%) followed by green algae, while chlorophyceae (62.29%) dominated during monsoon period. Zooplankton was represented mainly by copepoda and rotifera. A total of 27 genera of phytoplankton and 6 of zooplankton were recorded. Correlations with abiotic parameters have also been evaluated.